White Matter Dissection of the Fetal Brain - Horgos, Bianca; Mecea, Miruna; Boer, Armand; Szabo, Bianca; Buruiana, Andrei; Stamatian, Florin; Mihu, Carmen-Mihaela; Florian, Ioan Ştefan; Susman, Sergiu; Pascalau, Raluca (Frontiers in Neuroanatomy, 2020)
Neuroplasticity is a complex process of structural and functional reorganization of brain tissue. In the fetal period, neuroplasticity plays an important role in the emergence and development of white matter tracts. Here, we aimed to study the architecture of normal and hydrocephalus fetal brains by way of Klingler’s dissection. Ten normal brains and four pathological ones were collected from in utero deceased fetuses aged between 13 and 35 gestational weeks (GW). During this period, we observed modifications in volume, shape and sulci configuration. Our findings indicate that the major white matter tracts follow four waves of development. The first wave (13 GW) involves the corpus callosum, the fornix, the anterior commissure, and the uncinate fasciculus. In the second one (14 GW), the superior and inferior longitudinal fasciculi and the cingulum could be identified. The third wave (17 GW) concerns the internal capsule and in the fourth wave (20 GW) all the major tracts, including the inferior-occipital fasciculus, were depicted. In the pathological brains, fascicles in direct contact with the enlarged ventricles were displaced inferiorly and the corpus callosum convexity was inverted. Our results suggest an earlier development of the white matter tracts than estimated by DTI tractography studies. Correlating anatomical dissection with tractography data is of great interest for further research in the field of fetal brain mapping.